ANALYSIS OF INVENTORY MANAGEMENT OF PHARMACEUTICAL PRODUCTS AND CONSUMABLE MEDICAL EQUIPMENT IN KASIH BUNDA PUBLIC HOSPITAL - Sari, Alivia Nurlita; Basri, Mursyid Hasan (Journal of Business and Management, 2017)
Abstract. For several recent years, Indonesia’s healthcare spending is continually growing year by year along with increasing in Indonesia’s Gross Domestic Product. In the most of Indonesian hospital, pharmacy plays a vital role because it takes high contribution of total hospital expenditure. The reason is because pharmacy should procure and handle many pharmaceutical products and consumable medical equipment, which are critically important to patient’s life. While hospital expenditure is continually growing year by year, hospital pharmacy is required to provide good service in delivering pharmaceutical products and consumable medical equipment to patients. Consequently, pharmacy supply chain is expected to be done effectively and efficiently in order to decrease hospital expenditures while maximize their customer service level. This research aims to verify overstock and understock issues of pharmaceutical products and consumable medical equipment in Kasih Bunda Public Hospital which directly related to  hospital’s customer service level. Secondary data  about current inventory management was collected from hospital’s document during January 2017 until March 2017. This research uses continuous review policy to determine current inventory status by comparing average inventory level between actual and ideal scenario. Cycle Counting based on ABC Classification is also used to check inventory record accuracy in daily basis with aims at increasing productivity while decreasing inefficiencies. From the analysis, author found that most of pharmaceutical products and consumable medical equipment in Kasih Bunda Public Hospital are enduring excessive inventory. By using continuous review policy, Kasih Bunda Public Hospital has money saving potential as much IDR 542,857,077 which result from overstock value or about 48% of the total actual inventory value. Keywords: AIL, Continuous Review Policy, Cycle Counting, Inventory, Pharmacy